PENGARUH KARAKTERISTIK PEKERJAAN DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada Politeknik Ilmu Pelayaran Semarang) - Mohammad Sapta Heriyawan, 12.5202.0210; Setyowati, Widhy (Jurnal Mahasiswa Pasca Sarjana, 2015)
This Research have a purpose to explain the influence at job characteristic And enableness of officer to officer performance  mediation by Organizational Commitment at office of Semarang Merchant Marine Polytechnic. Research population is public servant of Civil at Semarang Merchant Marine Polytechnic, while sample use the technique of purposive sampling. Method  data collecting by using quesioner which   passed to a responder. Examination to research instrument done with the validity test ( analyse the factor) and test the reliabilitas with the coefficient alpha of appliance to statistic test by multiple regression analysis regresi, test the t, test  R2 and  mediation test. Result of research indicate that the Job characteristic have an effect on positive and signifikan to organizational commitment. Officer enableness have an effect is positive and signifikan to organizational commitment,  Job characteristic have an effect on the negativity   but  don,t signifikan to officer performance, Officer enableness have an effect is positive and signifikan to job performance, while Organizational Commitment, have an effect on positive to performance but  no signifikan. Keyword : Job Characteristic, Officer Enableness, Organizational Commitment, Performance.